2015
DOI: 10.1111/1346-8138.12978
|View full text |Cite
|
Sign up to set email alerts
|

Imbalance of T‐helper 17 and regulatory T cells in patients with alopecia areata

Abstract: There is mounting evidence that T helper (Th)17 cells and regulatory T cells (Treg) play parts in the pathogenesis of autoimmune disease. Hence, levels of these T-cell subsets in patients with alopecia areata (AA) merit investigation. Our goal was to assess Th17 and Treg levels in peripheral blood mononuclear cells (PBMC) and scalp lesions of patients with AA, correlating the findings with clinical characteristics. PBMC of 177 patients with AA (test group) and 42 healthy controls and scalp tissues of 33 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
70
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(70 citation statements)
references
References 26 publications
0
70
0
Order By: Relevance
“…11 IL-17 + cells are found around hair follicles, and significantly elevated circulating IL-17 levels and lower percentages of regulatory T cells (Treg) are seen in patients with AA. 12 Byun et al compared the effects of excimer laser treatment between the treated and untreated sides of an alopecic patch. However, only hair diameter was found to be significantly higher in the treated half, as improvements were seen on the control side as well.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 IL-17 + cells are found around hair follicles, and significantly elevated circulating IL-17 levels and lower percentages of regulatory T cells (Treg) are seen in patients with AA. 12 Byun et al compared the effects of excimer laser treatment between the treated and untreated sides of an alopecic patch. However, only hair diameter was found to be significantly higher in the treated half, as improvements were seen on the control side as well.…”
Section: Discussionmentioning
confidence: 99%
“…The mean age of the patients was 45.7 AE 16.9 years (range, 24-66) and the mean disease duration was 9.3 AE 8.1 years (range, 1-22). The treatments administrated to the patients included topical steroids (mean, 25 months; range, 3-60), infrared therapy (mean, 15.8 months; range, 9-30), topical immunotherapy (mean, 15.4 months; range, 7-29), corticosteroid pulse therapy and cryotherapy (mean, 11 months; range, [6][7][8][9][10][11][12][13][14][15][16]. In all cases, hair loss that extended beyond the scalp was used to confirm the diagnosis of AU.…”
Section: Methodsmentioning
confidence: 99%
“…Besides CD8+ and/or NKG2D+ cells, the role of additional immunocytes the immunopathology of AA has recently come under scrutiny, namely, that of regulatory T cells [45,46] and of perifollicular mast cells interacting with CD8+ T cells [47] (Fig. 2: AA pathobiology)(see Supplementary texts 3).…”
Section: Aa Disease Immunopathogenesismentioning
confidence: 99%
“…IL-2 is a key cytokine for T regulatory (reg) cell differentiation, homeostasis and functions [124]. In AA, an imbalance in the immune state of patients has been detected with altered T-helper cell and Treg cell functions [125,126]. A study by Shin et al revealed impaired function of CD4 T reg cells [127].…”
Section: Aldesleukinmentioning
confidence: 99%